Adobe Acrobat X for Windows and Macintosh : Visual QuickStart Guide - Deubert, John (Peachpit Press, 2010)
Adobe Acrobat X for Windows and Macintosh: Visual QuickStart Guide walks readers through tasks that are enhanced by numerous screenshots to teach beginning and intermediate users how to take advantage of the productive power of Adobe Acrobat. Author John Deubert takes readers through all of the basic Acrobat X features, from the basic tools used to create PDF documents and the newly enhanced review functionality, to the advanced tools that create digital signatures, interactive forms, and PDF Portfolios, plus a guide to Adobe's Acrobat.com online services. Beginning users will find a thorough introduction to this indispensable application, and Acrobat power users will enjoy a convenient reference guide that relies on straightforward language, clear steps, and practical tips to explore Acrobat's many capabilities. By the end of the book, users will be able to smoothly integrate Adobe Acrobat X into their workflow.